2022
DOI: 10.3390/ani12091113
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Replacement by a Blend of Vegetable Oils in Diets for Juvenile Tench (Tinca tinca Linnaeus, 1758): Effects on Growth Performance and Whole-Body Composition

Abstract: Among freshwater species, tench (Tinca tinca Linnaeus, 1758) is considered as a promising species for the diversification of aquaculture, but the intensification of techniques is necessary to promote and consolidate its culture. Adequate feeding in early growth phases is essential to face further grow-out. Fish oil (FO) is the main source of lipids in fish diets, but its production is unsustainable, and thus, alternative oils should be considered. A 90-day experiment was performed to evaluate the effects of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…In this experiment, this ratio varied between 0.75 and 0.92, corresponding to the control diet and 100% CO diet, respectively. These values were similar to those obtained by Sáez-Royuela et al [ 36 ] in juvenile tench fed diets with different substitutions levels of FO with a blend of vegetable oils. Linhartovà et al [ 49 ] reported higher values in the flesh of commercial-sized tench either under extensive culture (average weight 210 g, ΣPUFA/ΣSFA: 1.32) or semi-intensive conditions (average weight 680 g, ΣPUFA/ΣSFA: 1.10).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this experiment, this ratio varied between 0.75 and 0.92, corresponding to the control diet and 100% CO diet, respectively. These values were similar to those obtained by Sáez-Royuela et al [ 36 ] in juvenile tench fed diets with different substitutions levels of FO with a blend of vegetable oils. Linhartovà et al [ 49 ] reported higher values in the flesh of commercial-sized tench either under extensive culture (average weight 210 g, ΣPUFA/ΣSFA: 1.32) or semi-intensive conditions (average weight 680 g, ΣPUFA/ΣSFA: 1.10).…”
Section: Discussionsupporting
confidence: 90%
“…In the same way, Mzengereza et al [ 29 ] and Maldonado-Othón et al [ 19 ] reported a decrease in lipid content in muscle when camelina oil was included in the diet. In studies with juvenile golden pompano ( Trachinotus ovatus ) and juvenile tench, Guo et al [ 44 ] and Sáez-Royuela et al [ 36 ], respectively, found an association between body lipid content and dietary ALA/LA so that the lowest body lipid content coincided with the highest ALA/LA ratio. In our experiment, the same relationship was found, and the high lipid deposition corresponded to juveniles fed the control diet (ALA/LA = 0.25) whereas juveniles fed 100% CO (ALA/LA = 1.14) had lower lipid whole-body content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the aquaculture sector where up to 75% of the world's fish oil is used, leveraging the price of fish oil by partial substitution of vegetable oils could show economic incentives in the future. Therefore, studies have already been carried out in this line of research, finding that the substitution of fish oil with vegetable oils, including olive oil, does not significantly affect the nutritional strengths and impact on fish growth (Nasopoulou and Zabetakis, 2012;Sáez-Royuela et al, 2022). On the other hand, although global fish oil production is expected to increase until 2027 (Chouhan et al, 2020), recent studies indicate that global warming is causing substantial decreases of essential fatty acid v-3 in plankton, especially eicosapentaenoic acid (EPA), which would represent a loss of quality in fish feed and therefore in the nutritional quality of fish (Holm et al, 2022).…”
mentioning
confidence: 99%